Mycobacterium ulcerans-specific immune response after immunisation with bacillus Calmette-Guérin (BCG) vaccine. Issue 4 (22nd January 2021) - Pittet, Laure F.; Tebruegge, Marc; Dutta, Binita; Donath, Susan; Messina, Nicole; Casalaz, Dan; Hanekom, Willem A.; Britton, Warwick J.; Robins-Browne, Roy; Curtis, Nigel; Ritz, Nicole; ,
Highlights: Infant BCG immunisation induces M. ulcerans -specific immune responses. M. ulcerans - and M. tuberculosis -specific immune responses are qualitatively similar. Magnitude of M. ulcerans -specific immune responses was not influenced by BCG strain. These in-vitro findings support the protective effect observed epidemiologically. Abstract: Background: Bacillus Calmette–Guérin (BCG) vaccine provides partial protection against Buruli ulcer caused by Mycobacterium ulcerans in epidemiological studies. This study aimed to quantify M. ulcerans -specific immune responses induced by BCG immunisation. Methods: Intracellular cytokine analysis of in-vitro experiments done 10 weeks after BCG immunisation in 130 Australian infants randomised to one of three BCG vaccine strains given either at birth (BCG-Denmark, BCG-Japan, or BCG-Russia) or at two months of age (BCG-Denmark). Results: Proportions of polyfunctional CD4 + T-cells were higher in M. ulcerans -stimulated compared to unstimulated control samples. These proportions were not influenced by the vaccine strain or timing of the immunisation. The M. ulcerans -specific immune responses showed similar patterns to those observed in M. tuberculosis -stimulated samples, although they were of lower magnitude. Conclusions: Our data show that BCG immunisation induces M. ulcerans -specific immune responses in infants, likely explaining the cross-protective effect observed in epidemiological studies. (ACTRN12608000227392)